Геодинамическая обстановка формирования верхневендских песчаников на юго-западной окраине Восточно-Европейской платформы - Сокур, Т.М. (Видавничий дім "Академперіодика" НАН України, 2008)
Based on the petrochemical characteristics, the geodymanic mode of formation of sediments is reconstructed for the Upper Vend sandy rocks of the south-western margin of the East-European platform (the Dniester pericraton region).